2019
DOI: 10.1140/epjp/i2019-12803-y
|View full text |Cite
|
Sign up to set email alerts
|

Dark energy effects on charged and rotating black holes

Abstract: Using canonical typicality method, we reconsider the study of dark energy effects on four dimensional black holes. Concretely, we investigate the associated influences on the spectrum of various black hole backgrounds including the charged and the rotating ones. For such black hole solutions, we first elaborate analytically the corresponding radiation spectrum, the Hawking temperature and the dark information. Then, we discuss and analyze the corresponding findings. This work, recovering the results of the Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…where indicates the emission frequency [34]. It is noted that T out is the Hawking temperature for the Schwarzschild-Tangherlini with DE [35]. Such a temperature reads as…”
Section: Energy Emission Ratementioning
confidence: 99%
“…where indicates the emission frequency [34]. It is noted that T out is the Hawking temperature for the Schwarzschild-Tangherlini with DE [35]. Such a temperature reads as…”
Section: Energy Emission Ratementioning
confidence: 99%
“…Effectively, the quintessence, with intensity α, corresponding to the range −1, − 1 3 considered as a scalar field having negative pressure has been introduced to investigate the DE effects on the black hole physics [26,27,28]. Among others, it has been suggested that DE can be considered as a cooling mechanism affecting the black hole thermodynamical behaviors [29,30].…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…These questions may concern the dark sector associated with the dark matter [23] and the dark energy of late-time cosmology [24]. As a way to investigate the models dealing with such as a sector, a scalar field is usually introduced [25,26]. Concretely, the quintessence remains the simplest and the promising one [27][28][29].…”
Section: Introductionmentioning
confidence: 99%